2007
DOI: 10.1080/13550280701258084
|View full text |Cite
|
Sign up to set email alerts
|

Glial activation and matrix metalloproteinase release in cerebral malaria

Abstract: Although neurological symptoms associated with cerebral malaria (CM) are largely reversible, recent studies suggest that lasting neurological sequelae can occur. This may be especially true for children, in whom persistent deficits include problems with memory and attention. Because the malaria parasite is not thought to enter the brain parenchyma, lasting deficits are likely related to factors including the host response to disease. Studies with a rodent model, and with human postmortem tissue, suggest that g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 78 publications
0
28
0
Order By: Relevance
“…These molecules have not been studied yet in human malaria. However, in CM murine models, MMP-2 mRNA and protein were upregulated in brain [18] and MMP-7 mRNA was increased in liver but not in brain [18], whereas MMP-7 protein was increased in brain [19]. …”
Section: Involvement Of Mmp-9 In Complicated Severe Malariamentioning
confidence: 99%
See 1 more Smart Citation
“…These molecules have not been studied yet in human malaria. However, in CM murine models, MMP-2 mRNA and protein were upregulated in brain [18] and MMP-7 mRNA was increased in liver but not in brain [18], whereas MMP-7 protein was increased in brain [19]. …”
Section: Involvement Of Mmp-9 In Complicated Severe Malariamentioning
confidence: 99%
“…In the last decade, growing evidence on involvement of MMPs in falciparum malaria became available: human postmortem studies showed enhanced protein levels of MMP-1 in brains of CM patients [15], whereas MMP-8 was found increased in plasma of severe malaria patients [16]; additionally, activation of the human MMP-9 gene by P. falciparum has been reported in microarray studies on whole blood from children with malaria [17]. Interestingly, a role for MMPs during malaria is suggested also by evidence from nonhuman models of CM: in the brain of mice infected by P. Berghei ANKA, the etiological agent of murine CM, increased MMP-2, MMP-7, and MMP-9 levels, and pro-MMP-9 activation were found [18, 19]. …”
Section: Introductionmentioning
confidence: 98%
“…N euroinflammation, including astrogliosis and production of proinflammatory cytokines and chemokines, is a common finding following viral, bacterial, and parasitic infections of the CNS in both children and adults (1)(2)(3)(4)(5)(6)(7)(8)(9). Neuroinflammatory responses are also observed in autism, Alzheimer's disease, and other neurological diseases of unknown etiology (10 -14).…”
Section: Analysis Of the Neuroinflammatory Response To Tlr7 Stimulatimentioning
confidence: 99%
“…Although differences between human and mouse pathology require cautious interpretation, observations in mouse models of experimental CM (ECM) show glial cell activation in the brain1213. There are not many studies analysing microglia during ECM, one of them has shown that depletion of cells expressing the chemokine receptor, CX3CR1, which includes microglia, during a PbA infection suggests that they may not play a decisive role in ECM, although they can interact with T cells14.…”
mentioning
confidence: 99%